IDENTIFIKASI KERAGAMAN GENETIK SORGUM LOKAL HASIL IRADIASI MENGGUNAKAN PENANDA MOLEKULER RPAD - Arum, Laras Sekar; Ramadhan, Moch. Alfian Rizky; Hazmi, Muhammad; Murtiyaningsih, Hidayah (Politeknik Negeri Lampung., 2024)
Sorghum (Sorghum bicolor L. Moench) is an alternative food commodity with significant potential for development in Indonesia. However, its genetic diversity in Indonesia is relatively low. The low genetic diversity of sorghum prompts efforts to improve and search for new sources of genetic diversity, including through plant breeding. Radiation-induced mutation is a plant breeding technique aimed at obtaining new traits that are not present in the parent plants. Gamma ray irradiation can damage DNA, and during the repair process, DNA undergoes new mutations induced randomly. This study aims to investigate the agronomic characteristics, genetic diversity, and relationship among plants that have been irradiated with gamma rays using the Random Amplified Polymorphic DNA (RAPD) molecular markers. In this study, local sorghum varieties from Bandung, Demak, and Jember were subjected to gamma ray irradiation at doses of 0 Gy, 300 Gy, and 500 Gy to induce genetic diversity. The application of gamma ray irradiation doses had a significant impact on parameters such as viability, vigor, and morphology. The isolated DNA was analyzed using the Random Amplified Polymorphic DNA technique. OPA-12 showed the highest level of polymorphism among the four primers used. The bands produced by the four scored primers were analyzed using the NTSYSpc program to determine the level of relatedness between genotypes. The genetic distance between genotypes was considerably wide, ranging from 0.1 to 0.46, indicating the potential for crossbreeding